Peran Corporate Social Responsibility Pt Astra Dalam Pengembangan Pendidikan Lokal: Studi Kasus Program Astra Cerdas Di Pasangkayu - Juniva; Eva Afrilia; Adinda Prameswary Putry; Nuramanda Rizkiyah; Wilda; Alya Sasabila Yabiy; Rachmad; Nasrullah (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Educational access disparities in plantation areas remain a structural problem that has not been fully addressed by public services. This study aims to analyze the implementation of the Astra Cerdas Program as a form of Corporate Social Responsibility (CSR) by PT Astra Agro Lestari through PT Pasangkayu in Martajaya Village, Pasangkayu Regency, West Sulawesi, as well as to identify the factors that support and hinder the program's success. A qualitative descriptive approach was employed through field observation, in-depth interviews with stakeholders, and documentation review. The findings indicate that the Astra Cerdas Program operates multidimensionally, encompassing academic scholarships, incentives for contract teachers, strengthening of affiliated school facilities, and non-formal education interventions specifically targeting the indigenous Bunggu community. The program's success is supported by the company's long-term institutional commitment, cross-sector coordination among the private sector, schools, communities, and local government, as well as a program design grounded in the actual needs of the local community. On the other hand, obstacles encountered include geographic infrastructure limitations, funding vulnerability that remains dependent on CSR allocations, uneven distribution of educational facility assistance, and program monitoring capacity that requires further strengthening. This study affirms that strategic partnerships between corporations and local governments hold significant potential in expanding an inclusive and sustainable educational ecosystem in remote areas surrounding plantation industrial zones.